[OP.8C.07] RETINAL ARTERIOLAR WALL-TO-LUMEN RATIO IS USEFUL IN THE MANAGEMENT OF MASKED TREATED HYPERTENSIVE PATIENTS. (September 2017) - Gallo, A.; Mattina, A.; Kanaga, C.; Girerd, X.; Rosenbaum, D.
Abstract : Objective: The management of masked arterial hypertension (AH)in treated hypertensive patients is challenging. As other AH profiles, masked AH is associated to retinal microvascular changes, which may take place in different timings. We have recently observed an increased Wall-to-Lumen Ratio (WLR) in retinal arterioles of patients with masked AH. Our aim was to evaluate retinal arteriolar remodeling changes before and after Blood Pressure (BP) control improvement in masked AH. Design and method: 30 treated hypertensive patients (15 with masked AH, 15 with controlled AH) were consecutively enrolled and evaluated at baseline and after 6 months. Assessment included office and home BP measurements as well as Adaptive Optics RTX1® Camera imaging (ImagineEye, Orsay, France) that was used to measure Wall Thickness (WT), Internal Diameter (ID), Wall Cross Sectional Area (WCSA) and WLR. Controlled AH was defined as office BP < 140/90 mmHg and home BP < 135/85 mmHg, whereas masked AH was defined as office BP < 140/90 and home BP> = 135/85 mmHg. In patients diagnosed with masked AH, antihypertensive treatment was increased after baseline visit. Results: At baseline mean office Systolic BP (SBP) and Diastolic BP (DBP) were normal in both groups but resulted higher in masked AH compared to controls; home BP in masked AH patients was expectedly increased (Table). Figure. No caption available. WLR in masked AH patients was higher than controls (0.339 ± 0.07 vs 0.288 ± 0.04, p = 0.03) while other retinal arteriolar parameters did not differ (Table). In masked AH, at 6 months follow-up we observed a significant decrease in both office BP (SBP −43% and DBP −8%, respectively) and home BP (SBP −14% and DBP −23%). In this group, while WT and WCSA remained stable, a statistically significant reduction in WLR (−8.6%, p = 0.034) was observed due to lumen dilatation (+6.3%, p = 0.007). No changes in BP or in retinal arteriolar anatomical indexes were found in the control group. Conclusions: WLR is increased in masked AH. The increase of antihypertensive therapy that leads to an improved home BP control is associated to a decrease in WLR. Retinal arteriolar remodeling analysis with Adaptive Optics may be useful in the management of masked AH.